Security and a Financial Theory of Investment: Comment - Mendelson, Morris (Quarterly Journal of Economics, 1962)
Journal Article Security and a Financial Theory of Investment: Comment Get access Morris Mendelson Morris Mendelson University of Pennsylvania Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 76, Issue 2, May 1962, Pages 311–315, https://doi.org/10.2307/1880823 Published: 01 May 1962